Objective Imaging Diagnostics for Dry Eye Disease - Sang Beom Han; Yu-Chi Liu; Karim Mohamed-Noriega; Louis Tong; Jodhbir S. Mehta (Journal of Ophthalmology)
Traditional diagnostic tests for dry eye disease (DED), such as fluorescein tear film break-up time and the Schirmer test, are often associated with poor reproducibility and reliability, which make the diagnosis, follow-up, and management of the disease challenging. Advances in ocular imaging technology enables objective and reproducible measurement of changes in the ocular surface, tear film, and optical quality associated with DED. In this review, the authors will discuss the application of various imaging techniques, such as, noninvasive tear break-up time, anterior segment optical coherence tomography, in vivo confocal microscopy, meibography, interferometry, aberrometry, thermometry, and tear film imager in DED. Many studies have shown these devices to correlate with clinical symptoms and signs of DED, suggesting the potential of these imaging modalities as alternative tests for diagnosis and monitoring of the condition.